Towards sustainable governance of freshwater sand – A resource regime approach - Tahmina Yasmin; Julian Clark; Greg Sambrook Smith; Afrah Daham; Andrew Nicholas; Andrea Gasparotto (Earth System Governance, 2024)
The UN (2022) recently highlighted the global crisis posed by governance failures in sand mining. Yet despite this acknowledgement of its importance in unlocking this emerging crisis, research on sand governance has barely begun (Cao and Masanet, 2022). Recognizing governance as crucial to achieving sustainable freshwater sand mining, we bring together natural resource regime theory with the leveraging literature to elaborate the novel conceptual framework of the freshwater sand resource regime. This governance regime brings together black letter resource law and regulation, extraction and consumption practices of actors and societal values and behaviours to foster synergies and trade-offs for multi-scaled collective action over freshwater sand. Using a multisite research-commodity chain analysis case study of the Someshwari river in the Ganges-Brahmaputra basin, one of the most heavily mined river complexes in the world, we show the potential of this framework to identify leverage points among stakeholders to promote sustainable freshwater sand extraction and consumption practices. We demonstrate the framework's utility to align governance with UN Sustainable Development Goals for resource management. The research highlights the urgent need for further exploration of freshwater sand governance in different empirical contexts, given its potential implications for instilling global sand sustainability.